Migrants' rights: problems remain - N. A. Voronina (Управление)
The article considers the process of human rights regulatory development since the mid XXth century and adoption of social and legal responsibility by states in relation to migrants. The author analyses the legal status of migrants on the territory of the Russian Federation, European Union countries, the USA. The paper raises a wide range of issues related to granting socioeconomic rights and ensuring access to medicine to former compatriots, who returned to Russia and their children. The study notes that in recent years, Western countries have been reviewing approaches to state regulation of the social sphere, which in some cases discriminates towards refugees and displaced persons from other countries. The paper estimates the impact of the global epidemiological crisis caused by the COVID-19 pandemic on the socio-economic situation of migrants, the provision of medical and social assistance to the population of countries. The author concludes that in the context of COVID-19 pandemic states should provide migrants with free medical care and find effective social support mechanisms. The pandemic should not be used as a justification to undermine the guarantees of migrants’ rights.